PENERAPAN STRATEGI THINK TALK WRITE (TTW) DALAM PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIID SMP NEGERI 18 PEKANBARU - ', Asmarita; Saragih, Sehatta; ', Zuhri D (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was based on the student achievement in learning mathematics especially grade VIID SMP Negeri 18 Pekanbaru still get poor result. This fact indicated by the result of the test only 40,54% on the test about Set. This research is a class action reaserch. This research aims to improve the learning process and improve learning result in mathematics in grade VIID SMP Negeri 18 Pekanbaru by implementation of think talk write strategi of the learning model cooperative type of student team achievement division (STAD). The subject of this research were the students in the class VIID SMP Negeri 18 Pekanbaru at the second semester of academic year 2016/2017. The instruments of data collection were observation sheets that used to observe teacher and students activities during the learning process and students mathematic tests. The observation sheets were analyzed in descriptive narative, while the students mathematic tests were analyzed in statistic descriptive. The descriptive showed an improvement of learning process prior to the action on the first and second cycles. The result of data analysis show an increasing number of student learning mathematic from the basic score is 40,54% to 54,05% on the first test and 62,16% on second test. Based on the result of data analysis could be concluded that the impelemtation of think talk write strategy in cooperative learning type of STAD approach can improve mathematic learning process and learning outcomes in grade VIID SMP Negeri 18 Pekanbaru in the second semester of academic year 2016/2017.Key Word : Students Math Achievement, Think Talk Write Strategi, Cooperative Learning Type of STAD.